Penerapan Model Pembelajaran STEM (Science, Technology, Engineering, dan Math) dalam Konteks Biologi untuk Meningkatkan Motivasi Belajar Siswa - Kusumayadi, Kusumayadi (Biocaster : Jurnal Kajian Biologi, 2025)
Biology learning aims to develop students' thinking skills and problem-solving skills, so that students can understand biological concepts, solve problems, apply biological reasoning, and communicate solutions systematically. The purpose of this study was to improve students' learning motivation through the application of the STEM (Science, Technology, Engineering, and Math) learning model. This type of research uses Classroom Action Research (CAR) which is carried out in two cycles. The subjects of this study were 32 students of class XI of SMA Negeri 1 Kerambitan. The research instrument used was a motivation questionnaire. This Classroom Action Research (CAR) uses quantitative data analysis techniques. The results of the study in cycle II showed that students' learning motivation after being given action using STEM (Science, Technology, Engineering, and Math) increased from low to good criteria. So it is concluded that the STEM (Science, Technology, Engineering, and Math) learning model has succeeded in improving the learning motivation of class XI students of SMA Negeri 1 Kerambitan.